Periphyton community structure in the floating-net cage in the Koto Panjang Dam, Kampar Regency, Riau Province - Dwi Atmawati; Eni Sumiarsih; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is a type of algae that commonly inhabit the surface of immersed objects. A research aims to understand the periphyton community (types and abundance) in the floating-net cage in the Koto Panjang Dam has been conducted from May to June 2015. Samplings were conducted 3 times in 3 stations, namely St. I (Tanjung Alai, 50-200 cages), St. II (Pulau Gadang, 200-500 cages) and St. III (Dam Site , 500-700 cages). Periphyton samples were taken by scraping the surface of the immersed cage using tooth brush (10x10 cm2). Periphyton collected were then preserved in lugol 2-3 drop/40 ml and then was identified based on Hiroyuki (1977), Yunfang (1995), Sachlan (1982) and Bellinger and Sigee (2010).Result shown that there were 49 periphyton species present and they are belonged to 6 classes, namely Bacillariophyceae (15 species), Chlorophyceae (18 species), Chrysophyceae (1 species), Cyanophyceae (13 species), Dinophyceae (1 species) and Xanthophyceae (1 species) and the periphyton abundance was 35,945-60,690 cells/ cm2). In general, the H’ was 4.694-4.974; C was 0.038-0.052 and E was 0.890-0.917. The water quality parameters are as follows: temperature was 30-31 0C; brightness was 100.5-139.0 cm; turbidity was 1.50-2.68 FTU; pH was 5-6; DO was 5.6-6.0 mg/L; free CO2 was 3.9-4.5 mg/L; nitrate was 0.045-0.050 mg/L and phosphate was 0.035-0.041 mg/L. Based on periphyton community it can be concluded that the aquatic environment in the Koto Panjang Dam balance.Keyword : Peryphyton,Koto Panjang Dam, Kampar